2016
DOI: 10.1007/s13205-016-0394-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of low-density polyethylene (LDPE) by Aspergillus clavatus strain JASK1 isolated from landfill soil

Abstract: Polythene and plastic waste are found to accumulate in the environment, posing a major ecological threat. They are found to be considered non-degradable, once it enters the environment it has been found to remain there indefinitely. However, significant attention has been placed on biodegradable polymer, identification of microbes with degradative potential on plastic material. The aim of the present investigation was to biodegrade low-density polyethylene (LDPE) using potential fungi isolated from landfill so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(120 citation statements)
references
References 20 publications
5
89
0
8
Order By: Relevance
“…The sequence being novel was submitted to GenBank. For phylogenetic analysis, the fungal isolates’ ITS gene sequences from this work and other sequences retrieved from the database were aligned using the software CLUSTAL W 1.830. The phylogenetical analysis was made using the neighbor-joining method.…”
Section: Methodsmentioning
confidence: 99%
“…The sequence being novel was submitted to GenBank. For phylogenetic analysis, the fungal isolates’ ITS gene sequences from this work and other sequences retrieved from the database were aligned using the software CLUSTAL W 1.830. The phylogenetical analysis was made using the neighbor-joining method.…”
Section: Methodsmentioning
confidence: 99%
“…The rate and efficiency of polymer degradation were determined by pH alteration in media, CO 2 evolution, weight loss, SEM and FT-IR analysis. Similarly, Gajendiran et al (2016) isolated a fungus from landfill soil, identified as A. clavatus (strain JASK1). They exploited A. clavatus for LDPE degradation by incubating the samples for 90 days and evaluated the biodegradation by means of CO 2 evolution, SEM and AFM analysis.…”
Section: Polyethylenementioning
confidence: 99%
“…Biodegradation of Polythene bag and plastic cup by Rhizopus sps have been reported (Kannahi and Sudha 2013). In this study, we have chosen fungus for bioremediation because they are very versatile and play a crucial role in the decay of lignocelluloses polymer, and have extensive metabolic capabilities (Gajendiran et al 2016). Degradation of low density polyethylene by Rhizopus oryzae NS5 has not done yet.…”
Section: Introductionmentioning
confidence: 99%